Hypervelocity Launchers - Seiler, Friedrich; Igra, Ozer (Shock Wave Science and Technology Reference Library ;, 2016)
In the present volume numerous descriptions of Ram accelerators are presented. These descriptions provide good overview on the progress made and the present state of the Ram accelerator technology worldwide.  In addition, articles describing light gas gun, ballistic range including a chapter dealing with shock waves in solids are given. Along with the technical description of considered facilities, samples of obtained results are also included. Each chapter is written by an expert in the described topic providing a comprehensive description of the discussed phenomena.  .